What do first-year university students in Ontario, Canada, know about First Nations, Métis, and Inuit peoples and topics? - Schaefli, Laura; Godlewska, Anne; Korteweg, Lisa; Coombs, Andrew; Morcom, Lindsay; Rose, John (2020)
Article Full text available here: http://journals.sfu.ca/cje/index.php/cje-rce/article/view/3247 We disseminated the Awareness Questionnaire to the first-year cohorts at 10 Ontario universities in 2014. Co-designed with over 200 First Nations, Métis, and Inuit educators and community members across Ontario, the survey investigated how students are learning to think about colonialism and its relationship to Indigenous peoples and Canadian society. Statistical analysis of 2,899 student responses reveals that first-year university students who graduated from Ontario high schools are substantially unaware of Indigenous presence and vitality. The majority of students do not understand the fundamental laws structuring conditions of life for First Nations, Métis, and Inuit people or the contributions Indigenous peoples make to all aspects of Canadian society. Although they know slightly more about what is happening with regard to Indigenous peoples today, students have little sense of the historical circumstances and forces that shape current events. Arguably, students are this ignorant because the Ontario K–12 curriculum, which remains deeply inadequate, is the primary source of information for most students. However, when students have opportunities to engage with Indigenous perspectives and topics, it can make a difference to what students know and think. These results indicate that curricular reform is key to eradicating mass ignorance but cannot occur in isolation. Teacher education programs must play a central role in enacting the promise of new curricular emphases.